2005
DOI: 10.1345/aph.1e589
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid and Renal Toxicity: Data from French Adverse Effect Reporting Database

Abstract: These cases emphasize the need for regular monitoring of renal function during zoledronic acid treatment, with particular attention to patients with preexisting impaired renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 12 publications
(8 reference statements)
1
46
1
Order By: Relevance
“…In the USA Food and Drug Administration (FDA) adverse event reporting system, Chang et al [7] reported 72 cases of renal dysfunction in patients treated with zoledronic acid, of who 27 required dialysis and 18 died. Other retrospective studies have also shown renal toxicities associated with zoledronic acid, 4 mg over 15 min [16,22,23,25]. In response to these renal safety concerns, zoledronic acid product-labeling has been amended to require mandatory renal function testing before and during treatment, dose reductions for mild-to-moderate renal impairment and contraindication for patients with severe renal impairment.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA Food and Drug Administration (FDA) adverse event reporting system, Chang et al [7] reported 72 cases of renal dysfunction in patients treated with zoledronic acid, of who 27 required dialysis and 18 died. Other retrospective studies have also shown renal toxicities associated with zoledronic acid, 4 mg over 15 min [16,22,23,25]. In response to these renal safety concerns, zoledronic acid product-labeling has been amended to require mandatory renal function testing before and during treatment, dose reductions for mild-to-moderate renal impairment and contraindication for patients with severe renal impairment.…”
Section: Introductionmentioning
confidence: 99%
“…bisphosphonates such as zoledronic acid. 24,[26][27][28][29] Thus, ibandronate may be a viable option in preventing bone loss especially in patients with pre-existing renal damage or those who develop renal insufficiency during the course of their allo-SCT. Furthermore, this trial evaluated doses used to treat post-menopausal osteoporosis and using higher doses in our patient population may need to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen were hospitalized, eight received dialysis, and seven died [105]. The mechanism of nephrotoxicity is oftentimes multifactorial, considering that MM patients are more prone to develop renal complications secondary to the disease, hypercalcemia [93], and concomitant treatment with other potentially nephrotoxic drugs [105,106]. In order to prevent any deterioration in renal function, the 2007 ASCO guidelines [72] suggest adjustments in the administration of ZA for patients with a creatinine clearance of 30 -60 ml/minute, and it is not recommended for patients with severe renal impairment.…”
Section: Renal Toxicitymentioning
confidence: 99%